GAMBARAN PENYULUHAN DENGAN MEDIA POSTER DAN ANIMASI TERHADAP PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI PADA SISWA/I KELAS IV SDN 050736 PULAU BANYAK KECAMATAN TANJUNG PURA - Lusiani, yetti; Ridha, M Afdal (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
Counseling is an effort to provide information and explanations, which must be taken by everyone so that they can solve the problems they face and improve the quality of life. To facilitate counseling activities,media is needed. Media is an effort that can be used to channel messages from senders to recipients so that they can stimulate thoughts, feelings, attention and interests in maintaining optimal health. This study aims to determine the description of counseling with poster and animation media on knowledge about dental health care in fourth grade students of SDN 050736 Pulau Banyak, Tanjung Pura sub district, amounting to 30 peoples with a total sample of 30 students. The type of research used was descriptive with the survey method. The results of this study found that the level of knowledge of students about maintaining dental health before counseling with poster and animation media, namely 23 peoples (76.6%) were in the medium category. Then after counseling the level of knowledge of students about maintaining dental health with media posters has a good level of knowledge there were 8 students (53.3%) and with animation media have good level of knowledge, there were 15 students (100%). Based on this research, it can be seen that counseling using animation media was more effective than using poster media.